Peran generasi muda dalam menjaga hak asasi manusia - arisaputri, imelda islami (Maliki Interdisciplinary Journal, 2026)
Human Rights (HAM) are fundamental rights inherent in every individual from birth and must be protected by the state and respected by society. However, in practice, the enforcement of human rights in Indonesia still faces various challenges, such as discrimination, abuse of power, and low public awareness. This study aims to analyze the role of the younger generation in maintaining and upholding human rights amidst increasingly complex social dynamics. The method used in this research is a qualitative approach with a literature review of various relevant scientific sources. The results of the discussion indicate that the younger generation has a strategic role as agents of change in instilling human rights values. John Locke's thoughts on natural rights are an important basis for understanding the concept of human rights, while the values ​​of Pancasila provide a moral foundation for their implementation in Indonesia. The younger generation can contribute through increasing awareness, active participation in social activities, and utilizing digital media to advocate for justice and equality. Therefore, the involvement of the younger generation is key to creating a just, democratic society that upholds human rights.